Expanding the Cycad Horticulture Toolbox: Air Layer Protocols for Cycas Stems - Thomas E. Marler; Gil N. Cruz (Horticulturae)
Knowledge of propagation methods is crucial for conserving endangered plant species. Cycads are highly threatened, and propagation protocols using seeds and stem cuttings are well-understood. No air layer technique has been developed for cycad propagation, so the objective of this study was to develop a working protocol for adding this technique for cycad conservation. We opened wounds on mature Cycas edentata de Laub. stems to expose cortex and vascular tissue then installed an air layer medium to determine if adventitious roots would form. In one experiment, the peripheral vascular cylinder was exposed from 90° to 360°; in a second experiment, the use of auxin-promoting root stimulants was compared with a control group with no stimulants; and in a third experiment, the interior vascular cylinders were exposed in addition to the peripheral vascular cylinder. Every replication in every experiment developed adventitious roots beginning about 8 weeks and were ready to harvest with 10 cm roots by 14 weeks. The robust roots were about 1 cm in diameter, geotropic, and restricted to the outermost vascular cylinder exposed on the upper surface of the wounds. The number of roots and total root length per propagule increased by more than 300% as the percentage of exposed vascular tissue increased from 90° to 360°. Air layer techniques can be added to the cycad conservation toolbox, and its use may aid in conserving this threatened group of plants.